30‐day in vivo study of a fully maglev extracorporeal ventricular assist device. Issue 11 (3rd June 2022) - Li, Ping; Wu, Tingting; Hsu, Po‐Lin; Wei, Xufeng; Dong, Nianguo
Abstract: Objective: Cardiogenic shock (CS) often occurs in patients suffering from rapidly progressing end‐stage heart failure or acute myocardial infarction. Mechanical circulatory support may be used for patients who do not respond to medication or revascularization to stabilize hemodynamics. Extracorporeal ventricular assist device (Extra‐VAD) has been reported to be successful for patients with cardiogenic shock. This study aimed to evaluate the 30‐day in‐vivo performance and safety of a newly developed Extra‐VAD with maglev centrifugal pump technology, MoyoAssist®. Method: The study was conducted with 6 healthy ovine models, weighing 43.2 59.6 kg. Cannulation was performed with a 34 Fr venous cannula surgically connected to the left arterial appendage and a 24 Fr arterial cannula inserted into descending aorta. The pump flow rate was maintained at 2 3 L/min to provide sufficient cardiac support without suction. Activated clotting time was maintained within the range of 150 250 s. Results: No device‐related adverse events occurred throughout the study. Plasma‐free hemoglobin results were within the acceptable range of ventricular assist device therapy (<40 mg/dl). MGS01 had an anticoagulation management related bleeding event and was terminated on day 29. All other sheep's biochemical test results were stable. The autopsy showed no embolism or thrombus formation and no end‐organ damage. Conclusion: This study demonstrated that the MoyoAssist® Extra‐VAD is able to provide cardiac support effectively and safely and may provide a new alternative choice for patients with CS in China. Abstract :